Chapter 21 Effective Cooperation Between Strangers in Unexpected and Dangerous Situations A Matter of "Swift Trust" - Kjellevold Olsen, Olav (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter aims to discuss what it takes to make people or groups that do not know each other previously establish effective cooperation during unforeseen events. The focus is on the formation process of "swift trust", and the potential prerequisites and outcomes of such trust, seen as an alternative to traditional, history-based trust approaches that dominate the research literature of today. "Swift trust" may enable effective cooperation even among people that are unfamiliar with each other. This is seen as a relevant perspective because such temporal groups often handle unforeseen and critical events. Given the limited amount of research on "swift trust", the chapter also aims to identify future research questions. In the analysis, I utilize different theoretical perspectives, including the social sciences, experimental psychology and leadership, and seek to conclude the investigation by identifying different leadership strategies that may stimulate the formation of "swift trust"."